SISTEM INFORMASI PENGELOLAAN SURAT MASUK DAN SURAT KELUAR PADA DESA MALAPI KECAMATAN PUTUSIBAU SELATAN - Sigan, Agustinus; Hoendarto, Genrawan; Willay, Thommy (INTEKSIS, 2024)
Today's technology is at the core of every existing industry. Govermant’s office Malapi Putusibau is an industry engaged in Govermenet organisatio. In carrying out the filing of incoming and outgoing mail is still done manually and not computerized. In this paper, the author uses several research methods consisting of several components, namely research design using descriptive research design methods, data collection methods using interviews, observation and literature study, systems analysis techniques and system design techniques using Unified Modeling Language (UML). and application design techniques using the programming language HTML, CSS, javascript, and PHP. Application development using the XAMPP web server and MySQL as database storage. Based on the research conducted, a system of administrative transaction information for incoming and outgoing mail at Govermant’s office Malapi Putusibau was generated. Office is expected to assist in fast, precise and ackantorrate data processing. The conclusion is that the use of computer-based systems can improve service to kantorstomers through increasing company performance. The suggestions that can be given are the need for ackantorracy in entering data, the need for training system users and maintaining hardware and software that support the performance of the proposed system and the need for system evaluation if implemented. Keywords: Design, Incoming mail, Outgoing mail